Using video as an authentic material in improving students writing ability - Andi Kamariah (Center for Humanities and Innovation Studies, 2018)
This research aims to find out the impact of video as an authentic material on the writing ability. Also, this research aims to find out the use of video as an authentic material to created exciting writing for the secondary school students. The research employed a quasi-experimental method. Experimental group and control group were assigned different treatment. Each group consisted of 30 students. The sample was chosen by applying a cluster random sampling technique. The researcher used writing test both for control and experimental group. The data were analyzed using inferential statistics. In conducting the research, the writer used video as an authentic material as an instrument to improve the students’ writing ability particularly in writing a narrative paragraph which covered the five components of writing namely content, organization, vocabulary, language use, and mechanics. Besides, the researcher used a questionnaire to investigate the students’ interest in the use of video as authentic material. The research result showed that there was an improvement in the students’ writing ability between pretest and posttest in the experimental group after the treatment. This research reveals that the use of video as an authentic material was able to give a greater contribution to the students’ writing ability.